Laparoscopic Approach to Rectal Cancer—The New Standard? - Hsieh, Christine; Cologne, Kyle G. (Frontiers in Oncology, 2020)
Minimally invasive surgery has revolutionized the way surgeons perform colorectal surgery. Among other benefits, it is associated with decreased lengths of stay, wound and surgical site infections, pain scores, and has an overall lower complication rate versus open surgery (1.). Recently, however, the role of minimally invasive surgery has been called into question in the effective and safe treatment of rectal cancer. This manuscript will outline the history of minimally invasive rectal cancer surgery, examine evidence detailing its safety (compared with alternatives) and discuss important aspects of use (including the learning curve required to achieve proficiency, extent of its current use, and potential pitfalls). The current evidence suggests minimally invasive surgery is a very safe way to treat rectal cancer, when performed by experienced and specialty trained surgeons.